Villes globales et inégalités: Mondialisation ou financiarisation? - Olivier Godechot; Nicolas Woloszko (Luxembourg Income Study (LIS), 2021)
– Global cities' are urban areas which coordinate a dispersed global economy. As a consequence, they could fuel rising inequality. But do they really contribute to the increase in inequality? And, if so, what are the reasons? Is it because they are major metropolises, political decision-making centers, places of global coordination of production and trade of nonfinancial goods and services, or because they are financial centers? Based on the Luxembourg Income Study, we show that global financial centers contribute more than other urban areas to the increase in inequality, both at the national and local levels, and that this divergence is primarily the consequence of financialization rather than globalization.
Keywords: 330; inequality; wage distribution; regions